Reduction of tar, sulfur, chlorine and CO2 in syngas produced by gasification of refuse-derived fuel pellets - Matej Koritár; Juma Haydary (Scientific Reports)
Abstract Effective waste management is an increasingly urgent global challenge, with gasification emerging as promising alternative to conventional disposal methods. However, the major challenge in thermochemical waste processing is the presence of contaminants in the product streams. Therefore, this study focuses on the experimental gasification of refuse-derived fuel (RDF) pellets, with the aim of characterizing the products, analyzing contaminant distribution, and purifying the syngas from multiple contaminants simultaneously. Gasification experiments were conducted in a two-stage batch reactor, and the produced syngas was purified using two continuous packed absorption columns. Yields of gaseous, liquid, and solid products were 52.5%, 23.5%, and 7.3%, respectively. Resulting char exhibited a lower heating value (LHV) of 18.24 MJ/kg and retained 76.8% of the sulfur and 35.8% of the chlorine from the RDF. Heavy metal concentrations in the char remained below environmental limits. Syngas achieved a maximum LHV of 11.9 MJ/Nm3. Its purification using aqueous solutions of NaOH and methyl-diethanolamine achieved removal efficiencies of 97.77% for H₂S and 43.06% for COS. Efficiency of HCl removal with NaOH solution ranged from 82.15% to 89.27%, also contributing to CO₂ removal. Tar content in the syngas was significantly reduced through catalytic treatment with Ni/activated carbon, achieving a maximum removal efficiency of 85.89%. Concentrations of key contaminants in syngas were reduced to 6.13 ppm for H2S, 41.58 ppm for COS, 19.37 mg/Nm3 for HCl, and 2.11 g/Nm3 for tar. These results demonstrate the feasibility of integrated gasification and multi-contaminant purification for producing cleaner syngas from RDF, advancing sustainable waste-to-energy solutions.